Impact of antenatal synthetic glucocorticoid exposure on endocrine stress reactivity in term-born children - Alexander, Nina Carmen; Linke, Julia (The journal of clinical endocrinology & metabolism, 2012)
CONTEXT: Antenatal glucocorticoid (GC) exposure has been discussed as a potent programming factor of hypothalamus-pituitary-adrenal (HPA) axis activity, producing sustained alterations in cortisol secretion throughout life. So far, the assessment of HPA-axis activity in offspring of mothers treated with synthetic GC has been limited to a time period shortly after birth, with prematurity being an important confound in most prior studies. OBJECTIVE: The present study aimed to investigate HPA-axis reactivity of term-born children with antenatal GC exposure in a larger sample, allowing us to further address sex- and drug-specific effects. DESIGN, SETTING, AND PARTICIPANTS: This was a cross-sectional study comprised of 209 term-born children between 6 and 11 yr of age. Cortisol secretion patterns in response to a standardized laboratory stressor (Trier Social Stress Test for Children) were assessed in children with antenatal GC exposure (a single course of either dexamethasone or betamethasone) and compared to different control groups. RESULTS: We observed significantly increased cortisol reactivity to acute psychosocial stress in 6- to 11-yr-old, term-born children exposed to antenatal synthetic GC treatment compared to controls (F(3.4,345.9)=5.8; P<0.001). This finding appeared to be independent of the specific synthetic GC used and was found to be more pronounced in females. CONCLUSIONS: The present study provides the first evidence for long-lasting effects of antenatal synthetic GC exposure on HPA-axis reactivity in term-born children. These findings may bear important implications regarding the vulnerability for stress-related physical and psychiatric disorders, for which dysregulation of the HPA-axis has been discussed as a potential causal factor.